A different kind of synthesis: artificial synthesis of insulin in socialist China. (2nd October 2019) - Ling, Vivian; Jiang, Lijing
ABSTRACT: In the 1950s, the studies of proteins through their synthesis captured the attention of a number of biochemists. Among teams that set out to chemically synthesize the protein insulin, a large team in the People's Republic of China achieved success in 1966, months before the Cultural Revolution. By focusing on the ideological refashioning, material arrangement, and organizational style of the project, this paper addresses the political and material dimensions of the project, especially how it was reconstructed as an engineering project in-between biology and chemistry for the young republic. This case was different from the design rationales demonstrated in both American and German cases, in which insulin synthesis was viewed as either a challenging problem for biochemistry or primary research toward making synthetic fibers. The process reveals a fluid topography of the material, social, and political space that a group of biochemists could work with in socialist China.